SELJUKS’ KIRIM/SUĞDAK POLICY IN THE CONTEXT OF THE DEVELEPMENT OF ANATOLIAN TRADING - Yaşar BEDİRHAN (Fırat University, 2019)
Among the Turkey Seljuk State’s (1075-1318) sultans; I. Rukneddin Suleyman-shâh (467-478/1075-1086), I. Rukneddin Kilic Arslan (485-500/1093-1107), Sahinsâh (1110-1116) ve I. Rukneddin Mesud (510-550/1116-1155) devoted their life to conquer Anatolian lands, to found and organize the state by wars against The Crusaders, The Great Seljuks, and the other Turkish Tribes. These sultans are also called as founder sultans. Turkey Seljuk State’s(1075-1318) went under a rapid development period in political, military, economic, commercial, cultural and architectural aspects drom the late years of I. Rukneddin Mesud (510-550/1116-1155), and II. Rukneddin Kilic Arslan'dan (550-588/1156-1192). Founded in today’s Turkish Republic lands that have never lost its geopolitical and strategic importance but gains, Turkey Seljuk State (1075-1318) knew how to get benefit from these lands that is commercial bridge in the middle of three continents for ages. In this success, as much as geographical advantages followed policy’s importance could not be denied. In the world history- as today- trading has been of a great importance in order to develop a state. As the Turkey Seljuk Sultans knew it very well, to make progress in Anatolia they labored so much to develop commercial activities. Especially, they ensured the safety of trade routes passing through Anatolia, and they also tried to ensure sea trade routes that had connections with Anatolia. The most important sample of this was the expedition to Kirim done in the time of I. Alaaddin Keykubad. In order to handle Midle Asia Trade via Black Sea trade route, Turkey Seljuk State’s sultan I. Alaaddin Keykubad conquered Kirim, and ensured the safety of Blacksea trade route.